Chapter Hurrian Theophoric Names in the Documents from the Hittite Kingdom - de Martino, Stefano (Studia Asiana, 2023)
Hurrian personal names are documented among the members of the Hittite royal family starting from the time of King Tuthaliya I and they become more and more popular in the 13th century BC. The rulers of polities subordinate to Hatti, such as Karkemish and Amurru, bore Hurrian names. These names were also diffused among the inhabitants of Anatolia and Syria, as the Hittite texts and the tablets discovered at Alalah and Emar demonstrate. The greatest part of the Hurrian names is "Satznamen" in which one of the two components is a divine name. Thus, the name giving process can offer information on the spread of the Hurrian religious tradition in the regions under the Hittite political control.